Synthesis and characterization of single-walled carbon nanotubes by dual laser vaporization - Moodley, Mathew Kisten (My University, 2011)
A singular feature of research in carbon nanotubes which sets it apart from many other similar material systems, is the wide eld of promising applications ranging from molecular electronics and quantum computing to materials sci- ence and medicine. Fundamental studies of the nanotubes unusual properties combined with an arsenal of potential applications and cross-cutting collabora- tions between scientists and technologist from di¤erent disciplines, gave birth to what we now know as nanoscience and nanotechnology. However, there are several serious outstanding issues relating to carbon nan- otubes which has limited its full potential. The main issue is the inability to synthesize single-walled carbon nanotubes (SWCNTs) with a well-de ned atomic (n,m) structure, which is a critical parameter in determining whether the SWCNT is metallic or semi-conducting in nature. Under-pinning the lack of controlled synthesis, is a lack of the understanding of the growth mechanism leading to the nucleation and growth of carbon nanotubes. In this dissertation, the laser-furnace method was used to study the synthesis of SWCNTs. The investigations revolved around varying process parameters such as gas pressure, gas ow rate, furnace temperature and catalyst composition. A study was made on the e¤ect of varying these parameters on the synthesis of SWCNTs. To quantify these e¤ects, the as-prepared material was characterized by Raman spectroscopy, photoluminescence spectroscopy and electron microscopy. It was found that the variation of the argon gas pressure and ow rate in- uenced the quantity (in terms of mass collected) and quality (in terms of ID=IG (or ID=ID ) values) of as-prepared SWCNTs since these parameters af- fected the plasma dynamics. Low ow rates and low pressures, reduced the cross section for collisions between plasma constituents, in particular between C2 and the metal catalysts which a¤ected the probability of nucleation and growth of SWCNTs. The temperature, was found to be the critical process parameter in the nucleation and growth of SWCNTs. It was found that as the synthesis temperature was increased from 1073 K to 1373 K, the RBM inten- sities of Raman spectra increased indicating an increase in the nucleation and growth of SWCNTs. This correlated with the lowering of ID=IG (or ID=ID*) Page: ii values with increasing temperature. Overall, it was found that an argon pres- sure of 500 Torr, ow rate of 100 sccm and temperature of 1373 K, produced SWCNTs at a rate of 80 mg/h with the highest quality and the lowest ID=IG (or ID=ID ) value of 0.02 (0.25). The catalyst composition was changed by adding Fe, in steps of 0.5%. A shift to lower wavenumbers of the RBM spectrum was noted which pointed to the synthesis of nanotubes with larger diameters. This was attributed to an increase in the lattice parameter of the catalyst involved. However, continu- ously adding Fe to the catalyst saw a signi cant drop in RBM intensities and hence SWCNT content. We propose that this is due to an increase of FeCo alloy content in the target which was found to be detrimental to the synthesis process. It was found that with increasing synthesis temperature, the photolumines- cence (PL) intensities of the SWCNTs decreased. This was contrary to Raman spectroscopy results. It was concluded that as the synthesis temperature was increased from 1073 K to 1373 K, the laser-furnace method promotes the nu- cleation of metallic SWCNTs. The presence of metallic-SWCNTs are known to suppress PL emissions from semi-conducting SWCNTs. This showed that by controlling the synthesis temperature, either semiconducting-SWCNT or metallic-SWCNT could be promoted. To investigate nucleation and growth of SWCNTs, in situ optical emission spectroscopy (OES) was used to evaluate the temporal and spatial dynamics of C2, electron density (Ne) and electron temperature (Te). It was found that as the furnace temperature was increased from 1073 K to 1373 K in targets which contained catalysts,the concentration and lifetime of C2 in the plasma plume increased. Raman measurements on material collected from single-shot in situ OES measurements showed an increase in Raman RBM intensities and a corresponding decrease in ID=IG (or ID=ID ) values with increasing synthesis temperatures. This showed a direct correspondence between C2 lifetime and nucleation and growth of SWCNTs. In the absence of catalysts, C2 formed small graphene sheets or amorphous clusters. Contour plots of the Ne and Te showed a number of hot spots or local max- ima which increased in number with increasing temperature. We attribute the appearance of hot spots to the energy released when C2 was systematically consumed during the nucleation and growth of SWCNTs. Under the same experimental conditions, the ablation of a target containing no catalysts showed no hot spots in either of the Ne or Te maps and produced no SWCNTs. There- fore, we attribute the appearance of hot spots as a direct consequence of the nucleation and growth of SWCNTs.